Методологічні основи виділення міського правового простору - Мельничук, Ольга Степанівна; Мельничук, Ольга Степановна; Mel'nichuk, Ol'ga (Одеса : Юрид. л-ра, 2012)
The article deals with the analysis methodological grounds of the legal space concept formation in the modern legal philosophy. The necessity of distinguishing city legal space among such phenomenon as the state, regional, local and individual legal space is demonstrated. The city legal space has its own structure, specifics of development and correlation within the city's territory. City legal space is structured on the ground of the city's legal image and is based on the city legal onsciousness phenomenon which is connected with specific legal situations and events defining value-normative content of center-periphery relations in the limits of the city influence territory.
Мельничук О. С. Методологічні основи виділення міського правового простору / О. С. Мельничук // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 139-147.
Keywords: правовий простір; типи правового простору; міський правовий простір; компоненти міського правового простору; міська правова система; правовое пространство; типы правового пространства; городское правовое пространство; компоненты городского правового пространства; legal space; types of legal space; city legal space; components of city legal space; city legal system